2014
DOI: 10.1093/jac/dku321
|View full text |Cite
|
Sign up to set email alerts
|

Candida haemulonii complex: species identification and antifungal susceptibility profiles of clinical isolates from Brazil

Abstract: Our results reinforce the importance of molecular identification in differentiating species of the C. haemulonii complex. Moreover, the antifungal multiresistant profile of clinical isolates of the C. haemulonii complex represents a challenge to the treatment of such infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
86
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 16 publications
8
86
0
5
Order By: Relevance
“…We recommend that C. haemulonii complex isolates with high MICs to fluconazole be assessed for susceptibility to the other azoles. Echinocandins demonstrated excellent in vitro potency against the isolates (9,22). In the present study, our in vitro antifungal susceptibility data showed that MICs to echinocandins were low, indicating that there may be better treatment options.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…We recommend that C. haemulonii complex isolates with high MICs to fluconazole be assessed for susceptibility to the other azoles. Echinocandins demonstrated excellent in vitro potency against the isolates (9,22). In the present study, our in vitro antifungal susceptibility data showed that MICs to echinocandins were low, indicating that there may be better treatment options.…”
Section: Discussionsupporting
confidence: 46%
“…Overall, during the 5-year CHIF-NET study, C. haemulonii complex isolates represented 0.3% (31/9,673) of all yeast isolates, which was higher than the rate noted in the ARTEMIS study but similar to the rate found in Brazil (21,22). The identification and differentiation of C. haemulonii complex isolates relies on molecular methods, so it is difficult to compare the proportions because laboratories differ in the extent to which they identify uncommon Candida species to the species level; of laboratories that do identify to the species level, different methodologies are often used (8,9). In our study, we have reinforced that molecular methods are the preferred approach for definitive identification of members within the species complex.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations